Optimizing the configuration of a compact thermal facade module for solar renovation concept in buildings - Shen, Jingchun; Zhang, Xingxing; Yang, Tong; Tang, Llewellyn; Shinohara, Hiroyuki; Wu, Yupeng; Wang, Hong; Pan, Song; Wu, Jinshun; Xu, Peng (Elsevier, 2016)
Solar concepts show potentially an improved cost-performance (energy) ratio when applied as the integrated parts of building renovations. This paper reported a compact solar thermal facade (STF) module with the internally extruded flow channel suiting for solar renovation concept in buildings. A few of impact factors were considered for the parametric study in order to optimize the STF's configuration for various applications through the validated simulation model. The overall research results are expected to be useful for further improvement in the thermal performance of solar renovation measures.